Government and community empowerment RT 29 RW 08 Sawah Lebar Baru subdistrict in the formation and assistance of free organic waste management Group I - Yovan Witanto; Agus Nuramal; A Sofwan F Alqap (Dharmakayana, 2024)
The community needs education to change from the first behavior which usually un-separates waste to separate the organic types into non-organic types, even needs developing to have a 3R behavior, reduce, reuse and recycle. Educational activities for the community of the RT 29 RW 08, the village Sawah Lebar Baru were begun with socialization and distributing brochures. In the following week, a questionnaire was distributed to assess who had a better perception of waste among them to be collected and formed into a group. This group was directed to develop their perception into behavior; they were given a means of separating organic and non-organic waste. In the upcoming activity program, an assessment will be carried out on them to find out which ones give more time voluntarily to manage waste. Those who do so will be developed into compost producers or craftsmen of valuable objects from waste